Genotype x environment interaction and optimum resource allocation for yield and yield components of cassava - Dixon, Alfred G.O.; Nukenine, EN (1998)
Dry yield and yield components from 6 multilocational trials of cassava genotypes conducted for 3 years in Nigeria were used to study the nature and magnitude of genotype x environment (G x E) interaction and to determine the optimum resource allocation for cassava yield trials. The effects of environment, genotype and G x E interaction were highly significant for all yield traits. Variations due to G x E interaction were greater than those due to genotypic differences for all yield traits. Genotype x location x year interactions contributed most to the G x E interaction for all the yield traits. Therefore, to facilitate selection, zonation of cassava growing agroecologies into homogenous ecosystems using multivariate statistical approach should be done to minimise the influence of the G x E interaction. Testing at 3-5 locations for 2-3 years with 3-4 replications per location is the optimum combination that will not jeopardise precision in cassava yield trials.